Skin delivery of bioactive plant extracts through nanocarriers - Henriques Mota, Ana (2021)
In recent years, the scientific community has seen an increasing interest in the use of natural compounds in medicines, food supplements, cosmetics and dermatological products. An important example is Sambucus nigra L. whose flowers (elderflowers) and berries (elderberries) have been widely used in traditional medicine. The traditional use of elderflowers in the relief of early symptoms of common cold has been officially recognised by the European Union, where several products in the form of herbal tea, tincture or liquid extract, are available on the market. Elderberries have also been traditionally used in the form of herbal tea, syrup or juice. Nevertheless, no single herbal substance/herbal preparation is registered as medicine. In line with the need for comprehensive pharmacological studies to validate the traditional use of S. nigra, namely its anti-inflammatory activity, one of the aims of this PhD thesis was to screen and characterize biological activities of S. nigra L. extracts obtained using different extraction methodologies. Then, to optimize the biological activity of the best extract (i.e. with high interest for therapeutic uses), different extract-loaded nanocarriers were prepared. Different materials were applied in this task such as polymeric and lipid-based materials. In this specific context, the purpose of using nanotechnology as strategy was to increase the stability of bioactive compounds and to modulate their release, creating a potential topical formulation. Due to the harvesting time of elderflowers and elderberries, in a first part of this PhD thesis, initial nanoencapsulation studies were performed using hyaluronic acid as model drug. Hyaluronic acid is commonly used through intraarticular administration for viscosupplementation in osteoarthritis and other inflammation disorders. Therefore, the first studies consisted of producing an characterising polymeric nanoparticles made of poly(lacticco-glycolic acid) (PLGA) were prepared with and without hyaluronic acid. The inclusion of hyaluronic acid was achieved with an efficiency higher than 70%, but resulted in a marked particle size increase. Particles revealed an in vitro sustained release profile and in vitro cell compatibility, as well as a risk of haemolysis less than 1%, ensuring their safety. In vivo anti-inflammatory studies showed a higher inhibition for hyaluronic acid-loaded PLGA particles when compared to hyaluronic acid suspension (78% versus 60%). Results were not so different from the positive control, clearly suggesting that this formulation may be a promising alternative to the current hyaluronic acid injectable dosage form. Having characterised the intended particulate carrier, different extraction methods were studied to obtain the S. nigra extracts from elderflowers and elderberries. For this purpose, fresh flowers, and fresh and dried berries were considered, resulting in eighteen S. nigra extracts. Several parameters were considered for selecting the extraction method, i.e. yield of extraction, type of solvent, flavonoid content and biological activity of the resultant extracts (antioxidant activity, total polyphenol content, collagenase, elastase, tyrosinase and acetylcholinesterase inhibition). The most promising extracts were characterized for in vitro and in vivo anti-inflammatory activity and cytotoxicity (skin and monocytic cells). The most promising extracts were those obtained from fresh flowers using ultrasounds method with methanol. Specifically, these extracts showed results similar to positive controls, particularly the antioxidant activity (75 ± 2%), collagenase inhibition (94 ± 1%) and in vitro anti-inflammatory activity (97 ± 3%). Nevertheless, extracts of fresh flowers using ultrasounds/ethanol presented higher collagenase inhibition (88 ± 3%) and in vitro anti-inflammatory activity (102 ± 2%). Cytotoxicity testing confirmed their safety. The second aim of the present PhD thesis was to optimize the activity of the resultant methanolic extracts through encapsulation in different types of nanocarriers: polymeric nanoparticles based on PLGA and poly-Ɛ-caprolactone (PCL) and lipid-based nanoparticles (ethosomes). The so obtained nanoparticulate formulations were analysed in terms of particle size and morphology, physicochemical stability over the time, extract encapsulation efficiency, release profile and biological activities (e.g., anti-inflammatory activity, collagenase inhibition, antioxidant activity). Small and well-defined polymeric nanoparticles and ethosomes were prepared. The highest encapsulation efficiency (76%) was found in PLGA nanoparticles. The same happened for the anti-inflammatory activity (60.7 ± 9.0%). On the other hand, ethosomes presented a very promising value of collagenase inhibition. At the end, this thesis validates and supports the scientific evidence of potential uses of S. nigra as a therapeutic agent, in the case of polymeric nanoparticles, or as cosmetic ingredient, in the case of ethosomes. However, further studies should be carried out, hopefully attracting interest from pharmaceutical and cosmetic industries.